PENGARUH LAMA PERENDAMAN ZAT PADA BEBERAPA MODEL SAMBUNG PUCUK TERHADAP PERTUMBUHAN BIBIT KOPI (Coffea spp) - Pauline Ista Setyo Budi; Achmad Fatchul Aziez; Tyas Sumarah Kurnia Dewi (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2016)
The result of the research shows that the is to know the length of plant stimulus substance soaking in some coffee chupon grafting model doesn’t influence the coffee seeds growth.The writing of this thesis is based on the research which has been done in June 2012 to October 2012 in Mawar Lor,Jambu Subdistric,Semarang Regency. The research is implemented by using single factor with base pattern of complete Random Design and 3 times replication. This research uses 1 (one) treatment Factors in twelve combination. The results of this research are: 1) The leght of plant stimulus soaking in some coffee grifting models to coffee seeds growth doesn’t have effects in parameter of plan growth capacity observation (%),the amount of the leaves (sheet), the length of outermost leaf (cm), the width of outermost leaf(cm), and the height of the plant(cm), 2) The best result is on coffee seeds growth in side grafting with 2/3 of leaf by 30 minutes soakings.